Enabling social rights through proactive public policy: An academic auditing of education and health sectors in India - Dhal, Sangita (2016)
Socio-economic rights are enabling instruments of healthy democratic practices in every liberal society, which lead to empowerment of people in general and the marginalised and underprivileged sections of the society in particular. These rights compliment corresponding political and legal rights of citizens and thereby create conditions of good living. The founding fathers of the Indian Constitution had firm belief in providing these provisions in the form of well-intended objectives to bring about socio-economic justice. However, these rights were mostly enshrined in the Directive Principles of State Policy (DPSP) in Part-IV of the Indian Constitution, which are not justiceable. Despite political will, socio-economic rights could not find their due place in the category of justiceable rights because of the economic constraints of the post-colonial state. On the other hand, the emphasis on political and civil rights had its historical justification due to the legacy of the anti-colonial movement. The priority of the newly born Indian nation was political democracy for all rather than socio-economic democracy, which was a much more complex and gigantic task to be achieved. Hence political rights were incorporated as fundamental rights in the Indian Constitution. It is observed that though Indian democracy gathered momentum and strengthened its roots in political terms, consequent socio-economic democracy could not be achieved due to the subsequent political discourse in this country due to the perennial resource constraints and economic handicaps of the post-colonial state. However, things started moving in a positive direction in the last two decades. With the change in approach towards development and redistribution of wealth, the neo-liberal policies of the state in the globalisation era have adopted a new model of rights -based approach of social inclusion and equitable distribution of the fruits of development. It is in this context that this article critically examines the education and health policies of the state within the framework of the national goal towards greater socio-economic empowerment of all communities hitherto marginalised and alienated in the development narratives of post-independence India. - Reproduced.
Keywords: Social status - India; Health services - India; Education - India; Auditing - India; Public policy - India; Social status